2019
DOI: 10.22230/ijepl.2019v14n2a862
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School Administrator in Providing Early Career Teachers’ Support: A Pan-Canadian Perspective

Abstract: This article is based on an extensive mixed-methods pan-Canadian study that examined the differential impact of teacher induction and mentorship programs on the retention of early career teachers (ECTs). It discusses the findings from the analysis of publicly available pan-Canadian documents detailing the mandated roles, duties, and responsibilities of school administrators in teacher induction and mentorship. It then describes the results of the Teacher Induction Survey (N = 1,343) and the telephone interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As indicated by Kutsyuruba, Walker and Godden (2017), Kutsyuruba, Walker, Matheson and Bosica (2017), only 45 percent of mentees agreed or strongly agreed that the “school administrator took an active interest in their successful induction into teaching” (p. 31). Yet leaders are recognized as essential in establishing the structures and providing adequate resources for mentorship (Bayles et al , 2018; Squires, 2018; Walker and Kutsyuruba, 2019). Leadership includes not only the in-school administration who can leverage resources to support the development of the mentorship, but also the central administration who can provide additional resources, implement the district-wide initiatives such as induction programs, and elevate the status of these practices by championing mentorship throughout the district.…”
Section: The Role Of Leadersmentioning
confidence: 99%
“…As indicated by Kutsyuruba, Walker and Godden (2017), Kutsyuruba, Walker, Matheson and Bosica (2017), only 45 percent of mentees agreed or strongly agreed that the “school administrator took an active interest in their successful induction into teaching” (p. 31). Yet leaders are recognized as essential in establishing the structures and providing adequate resources for mentorship (Bayles et al , 2018; Squires, 2018; Walker and Kutsyuruba, 2019). Leadership includes not only the in-school administration who can leverage resources to support the development of the mentorship, but also the central administration who can provide additional resources, implement the district-wide initiatives such as induction programs, and elevate the status of these practices by championing mentorship throughout the district.…”
Section: The Role Of Leadersmentioning
confidence: 99%
“…As previously mentioned, this study is part of a longitudinal research program focused on examining trends in beginning teacher experiences in Alberta. It is designed around a common set of research-based professional and personal factors often considered when studying early career teaching experiences ( Andreychuk, 2019 ; Mansfield et al., 2016 ; Naidoo & Wagner, 2020 ; Walker & Kutsyuruba, 2019 ). Core questions that underscore each factor were developed for standard administrations with additional questions later developed and added, as warranted, to further assist the ATA to better understand how to address particular socio-political and economic conditions that may impact beginning teachers in the province.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that teacher retention is often highest when there are adaptive professional and personal factors ( Clandinin et al., 2015 ; Mansfield et al., 2014 ; Schafer, 2013 ). For early career teachers, professional factors of particular importance include high quality pre-service teacher programming, mentorship and professional development opportunities, collegial working relationships while in the field, and student and parental support (e.g., Kurtz & St. Maurice, 2018 ; Naidoo & Wagner, 2020 ; Walker & Kutsyuruba, 2019 ). In regard to personal factors, early career teachers should be provided with ample opportunities to develop coping strategies, communication skills, and stress management skills through workshops, mental health supports, and personal relationships (e.g., Andreychuk, 2019 ; Mansfield et al., 2016 ; McKay, 2019 ; Squires, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, teachers should act in a way to help students in their learning and acquisition, rather than making students learn ( Liu et al, 2018 ; Lazarides et al, 2019 ; Greenier et al, 2023 ). In fact, teachers are of pivotal importance when it comes to creating, maintaining, and influencing a safe learning environment in which students can learn effectively ( Walker and Kutsyuruba, 2019 ; Bishop et al, 2020 ; Valiente et al, 2020 ; Tvedt et al, 2021 ). As noted by Reeve and Shin (2020) , teachers hold authoritative positions during teaching, enabling them to shape and guide the behaviors and attitudes of learners.…”
Section: Review Of the Literaturementioning
confidence: 99%